Stable parallel algorithms for computing and updating the qr decomposition - Clarke, Michael R B; Kontoghiorghes, Erricos John (My University, 1993)
n this paper we propose new stable parallel algorithms based on Householder transformations and compound Given's rotations to compute the QR decomposition of a rectangular matrix. The predicted execution time of all algorithms on the massively parallel SIMD array processor AMT DAP-510, have been obtained and analyzed. Modified versions of these algorithms are also considered for updating the QR decomposition, when rows are inserted to the data matrix.
Keywords: Algorithms; Arithmetic; Parallel algorithms